1988
DOI: 10.5935/0305-7518.19880018
|View full text |Cite
|
Sign up to set email alerts
|

In vitromethods for determination of viability of mycobacteria: comparison of ATP content, morphological index and FDA-EB fluorescent staining inMycobacterium leprae

Abstract: Bacilli were purified from the 23 cases of multi bacillary type of leprosy. The ATP content of these bacilli was assayed by a firefly bioluminescent technique which is capable of detecting a very small number of cultivable mycobacteria as assessed by colony counts. The A TP content was compared with morphological index (MI) and FDA-EB staining of bacilli from the same specimens. It was observed that when MI was I % or more, the A TP content/solid bacillus was fairly constant in 15 cases studied. It ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Similar lack of correlation between BI/MI and other in vitro viability detection methods like FDA-EB staining, thymidine uptake and ATP assay have been reported. 4,8 Moreover in this study, in few particularly high BI cases, the cpm output was very inconsistent with BI (Table 1). Two likely explanations could be inhibition of metabolic activity by host tissue or suppression of metabolic activity due to competitive inhibition in the medium.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar lack of correlation between BI/MI and other in vitro viability detection methods like FDA-EB staining, thymidine uptake and ATP assay have been reported. 4,8 Moreover in this study, in few particularly high BI cases, the cpm output was very inconsistent with BI (Table 1). Two likely explanations could be inhibition of metabolic activity by host tissue or suppression of metabolic activity due to competitive inhibition in the medium.…”
Section: Discussionmentioning
confidence: 95%
“…[4][5][6] Jagannathan and Mahadevan 7 showed a good correlation between ATP and Fc receptor assay. Katoch et al, 8 found ATP, an easy and a better tool for viability determination than morphological index (MI) and ß uorescence di-acetate (FDA-EB) staining. Gupta et al, 6 found a good correlation with gene ampliÞ cation assay.…”
Section: Membersmentioning
confidence: 99%
“…leprae that is derived from SW-10 cells by measuring its ATP content (Fig 8). Katoch et al [24] have reported that the ATP content of cultivable mycobacteria, M . tuberculosis and M .…”
Section: Discussionmentioning
confidence: 99%
“…During recent years members of the M. fortuitum-chelonei complex have emerged as important human pathogens [1][2][3]. The characterization of this complex has been mainly based on analysis of phenotypic characters including biochemical and enzymatic markers, bacteriocin typing, antigens, cell wall lipids, and proteins [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%